Characteristics, Outcomes, and Cost Patterns of High-Cost Patients in the Intensive Care Unit. (2nd September 2018) - Reardon, Peter M.; Fernando, Shannon M.; Van Katwyk, Sasha; Thavorn, Kednapa; Kobewka, Daniel; Tanuseputro, Peter; Rosenberg, Erin; Wan, Cynthia; Vanderspank-Wright, Brandi; Kubelik, Dalibor; Devlin, Rose Anne; Klinger, Christopher; et al.
Abstract : Background . ICU care is costly, and there is a large variation in cost among patients. Methods . This is an observational study conducted at two ICUs in an academic centre. We compared the demographics, clinical data, and outcomes of the highest decile of patients by total costs, to the rest of the population. Results . A total of 7, 849 patients were included. The high-cost group had a longer median ICU length of stay (26 versus 4 days, P < 0.001 ) and amounted to 49% of total costs. In-hospital mortality was lower in the high-cost group (21.1% versus 28.4%, P < 0.001 ). Fewer high-cost patients were discharged home (23.9% versus 45.2%, P < 0.001 ), and a large proportion were transferred to long-term care (35.1% versus 12.1%, P < 0.001 ). Patients with younger age or a diagnosis of subarachnoid hemorrhage, acute respiratory failure, or complications of procedures were more likely to be high cost. Conclusions . High-cost users utilized half of the total costs. While cost is associated with LOS, other drivers include younger age or admission for respiratory failure, subarachnoid hemorrhage, or after a procedural complication. Cost-reduction interventions should incorporate strategies to optimize critical care use among these patients.